Experiences of Postpartum Depression in Pakistan: A Phenomenological Study - Mariyum Amjad; Dr Asma Majeed; Komal Imran (Research Journal of Psychology, 2025)
This current study was conducted to explore the experiences of postpartum depression in Pakistan. This is not a novel phenomenon in Pakistan; however, the societal norms and taboos have stigmatized it. Therefore, the aim of this study was to explore what women in Pakistan go through while dealing with postpartum depression. Previous researches in Pakistan have not been sufficient enough to highlight the postpartum women’s experiences, thus, rationalizing the need for this study. Adopting a qualitative approach, the study consisted of six participants (women residing in Lahore) who had experienced postpartum depression. The participants belonged to diverse backgrounds and with the help of in-depth semi-structured interviews, their experiences were collected. After a thorough thematic analysis, seven major themes emerged. The findings of the study shed light on the sufferings of women experiencing PPD, how their psychological, physical, and social well-being was compromised and how they managed it while overcoming the stigma of mental disorders in a country like Pakistan.